Artemisinin derivative DHA27 enhances the antibacterial effect of aminoglycosides against Pseudomonas aeruginosa by inhibiting mRNA expression of aminoglycoside-modifying enzymes - Wang, Nuoyan; Chen, Xuemin; Luo, Jing; Deng, Fei; Shi, Fuguo; Wu, Qin; Huang, Yasi; Ouyang, Qin; Qin, Rongxin; Zhou, Hong (Frontiers in Pharmacology, 2022)
Bacterial resistance is becoming increasingly serious, the present study aimed to investigate the mechanism of antibacterial sensitization effect of DHA27 combined with tobramycin in tobramycin-resistant Pseudomonas aeruginosa (PA). We found that DHA27 combined with aminoglycosides had an antibacterial sensitization effect on PA. Tobramycin, owing to its lower toxic and side effects, was selected to further study the molecular mechanism of drug combination. A sublethal-dose bacterial challenge/sepsis mouse model was established to study the protective effect of DHA27 plus tobramycin. Scanning electron microscopy was used to investigate whether DHA27 exerts the antibacterial sensitization effect by directly affecting bacterial morphology. The effect of DHA27 on daunorubicin accumulation in bacteria was studied, and quantitative reverse transcription PCR was used to study the effect of DHA27 plus tobramycin on 16S rRNA methyltransferase and aminoglycoside-modifying enzyme mRNA expression. Twenty clinical isolates of PA were found to be tobramycin resistant; DHA27 plus tobramycin had a significant antibacterial sensitization effect on many of these resistant strains. DHA27 plus tobramycin reduced the bacterial load in the spleen and lungs of sepsis model mice and levels of proinflammatory cytokines interleukin-1β and interferon-γ. DHA27 plus tobramycin significantly inhibited the mRNA expression of aminoglycoside-modifying enzymes in bacteria. DHA27 combined with AGs had an antibacterial sensitization effect on PA; the molecular mechanism underlying this effect is closely related to the inhibition of the mRNA expression of aminoglycoside-modifying enzymes, especially aac(3)-II.